Implementation of Station Rotation Learning Strategy in Improving Physical Activity and Learning Participation in Physical Education for Elementary School Students - Alaendra Afwan Desarva; Dian Budiana; Eva Sri Gumilang (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aims to determine the effect of implementing a station-based learning strategy (station rotation) on increasing physical activity and participation among fifth-grade students in physical education classes at elementary schools. This study uses a quantitative approach with a quasi-experimental design in the form of a pretest-posttest Control Group Design. The sample consisted of 31 fifth-grade students at State Elementary School 113 Banjarsari, Bandung, divided into an experimental group (n = 16) and a control group (n = 15), selected using purposive sampling. Physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C), and student participation was measured using an observation sheet. Data analysis included descriptive statistics, the Shapiro-Wilk normality test, the Levene homogeneity test, the Mann-Whitney U test for the physical activity variable, and N-Gain Score analysis. The results of the study showed that the experimental group experienced an increase in physical activity scores from an average of 2.68 (moderate category) to 3.44 (high category), while the control group’s scores decreased from 2.89 to 2.69. For the participation variable, the absolute posttest scores did not show a statistically significant difference (p = 0.40). However, the N-Gain Score analysis revealed a highly significant difference in the effectiveness of the improvement between the two groups (p = 0.000). The conclusion of this study is that a learning strategy based on evidence has proven effective in improving physical.